2018
DOI: 10.1016/j.ijscr.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Autonomously hyperfunctioning cystic nodule harbouring thyroid carcinoma – Case report and literature review

Abstract: HighlightsHyperthyroidism cannot rule out thyroid cancer.Published cases of autonomously functioning thyroid carcinomas are increasing.In hyperthyroid patients, carcinoma should always be considered as differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Indeed, one patient with follicular thyroid cancer, cared for in our institution (not included in the study population), initially presented with a hyperfunctional nodule which turned out to be malignant. Some studies such as a review by Mirfakhraee et al report malignancy rates of up to 3.1% for hyperfunctional nodules [27][28][29]. Further studies evaluating the malignancy rate of hyperfunctional nodules seem warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one patient with follicular thyroid cancer, cared for in our institution (not included in the study population), initially presented with a hyperfunctional nodule which turned out to be malignant. Some studies such as a review by Mirfakhraee et al report malignancy rates of up to 3.1% for hyperfunctional nodules [27][28][29]. Further studies evaluating the malignancy rate of hyperfunctional nodules seem warranted.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a total reliance on fine-needle biopsy without performing scintigraphy would result in surgery for benign nodules suspected of being malignant and may increase the surgical morbidity (29). Moreover, a systematic exclusion of malignancy in HTNs with fine-needle biopsy is presumed to not be cost-effective (30). Furthermore, HTNs cannot reliably be identified or excluded by the thyroid-stimulating hormone (TSH) level alone (31).…”
mentioning
confidence: 99%
“…However, whereas FNAC has become the gold standard for preoperative clarification of sonomorphologically suspicious TN, the role of scintigraphy is controversially defined in international guidelines [11,[22][23][24][25]. Scintigraphy is not considered to have a significant impact on the assessment of the risk of malignancy of TN despite the fact that it has been shown to almost rule out malignancy in cases of autonomously hyperfunctioning TN [26][27][28]. Furthermore, hyperfunctioning TN cannot be reliably identified or excluded by laboratory assessment alone [29,30].…”
Section: Discussionmentioning
confidence: 99%